进口油菜籽生产菜籽油过程中生育酚 和植物甾醇含量的变化 Changes in tocopherol and phytosterol contents during the production of rapeseed oil from imported rapeseed - 于雷1，孙玉萍2，符文志2，詹亚名2，仇长璐2，周敏2，黎锶华2 YU Lei1, SUN Yuping2, FU Wenzhi2, ZHAN Yaming2, QIU Changlu2, ZHOU Min2, LI Sihua2 (Zhongguo youzhi)
为开发高品质菜籽油加工工艺，以进口加拿大油菜籽为原料， 比较分析了压榨、浸出菜籽原油中生育酚和植物甾醇含量及其在精炼过程中的变化。结果表明：压榨菜籽原油中生育酚和植物甾醇含量分别为662~706 mg/kg和7 731~8 568 mg/kg，浸出菜籽原油中二者含量分别为774~885 mg/kg和9 177~10 136 mg/kg，两种菜籽原油中生育酚以γ-生育酚和α-生育酚为主；在菜籽油精炼过程中，生育酚和植物甾醇在各工段均有损失，总损失率分别为11.37%~18.84%和327%~11.89%，其中生育酚在脱臭工段损失最多，植物甾醇在中和工段和脱臭工段损失率较高；中和工段和脱臭工段菜籽油中生育酚各组分占比变幅大小顺序为α-生育酚>（β+γ）-生育酚>δ-生育酚，其中中和工段α-生育酚占比降低，（β+γ）-生育酚占比升高，脱臭工段与之相反；增加中和油的酸值，脱臭馏出物的酸值相应升高，生育酚含量降低。综上，浸出菜籽原油中生育酚和植物甾醇含量高于压榨菜籽原油，生育酚和植物甾醇在精炼各工段均有损失，通过适当控制脱酸程度，可减少菜籽油中生育酚损失。 In order to develop high-quality rapeseed oil processing technology, imported Canadian rapeseed was used as raw material to compare and analyze the contents of tocopherol and phytosterol in pressed and leached crude rapeseed oil, as well as the changes of these two indicators during the refining process. The results showed that the contents of tocopherol and phytosterol in the pressed crude rapeseed oil were 662-706 mg/kg and 7 731-8 568 mg/kg, respectively, and the contents of tocopherol and phytosterol in the leached crude rapeseed oil were 774-885 mg/kg and 9 177-10 136 mg/kg, respectively. The two types of crude rapeseed oil mainly containγ- tocopherol and α- tocopherol. During the refining process, both tocopherol and phytosterol in rapeseed oil were lost in each section, with total loss rates ranging from 11.37% to 18.84% and 3.27% to 11.89%, respectively. Among them, tocopherol had the highest loss in the deodorization section, while phytosterol had higher loss rates in the neutralization and deodorization sections. The changes in the proportion of each component of tocopherol in rapeseed oil in the neutralization and deodorization sections were in the order of α- tocopherol>(β+γ)-tocopherol>δ-tocopherol. The α-tocopherol proportion in neutralization section decreased, and (β+γ)-tocopherol proportion increased, and deodorization section was the opposite. Increasing the acid value of neutralized oil led to a corresponding increase in the acid value and decrease in tocopherol content of the deodorized distillate. In summary, the contents of tocopherol and phytosterol in leached crude rapeseed oil are higher than that in pressed crude rapeseed oil. Both tocopherol and phytosterol are lost in various refining sections. By appropriately controlling the degree of deacidification, the loss of tocopherol in rapeseed oil can be reduced.